Competition policy and intellectual property in today's global economy - Anderson, Robert D.; Carvalho, Nuno Ferreira de; Taubman, Antony (Cambridge : Cambridge University Press, 2021)
The fast-evolving relationship between the promotion of welfare-enhancing competition and the balanced protection of intellectual property (IP) rights has attracted the attention of policymakers, analysts and scholars. This interest is inevitable in an environment that lays ever greater emphasis on the management of knowledge and innovation and on mechanisms to ensure that the public derives the expected social and economic benefits from this innovation and the spread of knowledge. This book looks at the positive linkage between IP and competition in jurisdictions around the world, surveying developments and policy issues from an international and comparative perspective. It includes analysis of key doctrinal and policy issues by leading academics and practitioners from around the globe and a cutting-edge survey of related developments across both developed and developing economies. It also situates current policy developments at the national level in the context of multilateral developments, at WIPO, WTO and elsewhere.
Title from publisher's bibliographic system (viewed on 04 Jun 2021).
Keywords: Intellectual property; Antitrust law